TWEAK-binding autoantibodies are generated during psoriatic arthritis and are not influenced by anti-TNF therapy. Issue 1 (December 2016) - Guis, Sandrine; Berbis, Philippe; Stephan, Delphine; Bertin, Daniel; Amatore, Florent; Balandraud, Nathalie; Lesavre, Nathalie; Desplat-Jégo, Sophie
Abstract Background TNF weakly inducer of apoptosis (TWEAK) is member of the TNF ligand superfamily. Various data support that TWEAK produced by synovial macrophages may contribute to synovitis observed in psoriatic arthritis (PsoA). In PsoA, anti-TNF therapy has been successful in agreement with the key role of TNF in the pathogenesis and the generation by PsoA patients of anti-TNF autoantibodies referred as "beneficial autoimmunity to pro-inflammatory mediators". However, the role of TNF-alpha in the regulation of TWEAK modulation of inflammation during PsoA remains unknown. Methods We have studied level course during anti-TNF therapy of serum soluble TWEAK. In the same cohort, we have investigated the generation of TWEAK-binding autoantibodies by PsoA patients before and after anti-TNF therapy. Results Patients with PsoA had significantly higher serum levels of TWEAK compared with controls [respective means (±SEM) were 645 pg/ml (64) and 467 pg/ml (23); (p = 0.006)] but serum soluble TWEAK levels were not correlated with BASDAI (Spearman's coefficients <0.003, p > 0.05). Our study showed that soluble TWEAK levels were not modulated by etanercept therapy [respective Means (±SEM) were 605 (95) (week 12) and 744 (97) (week 24) pg/ml; (p > 0.23)]. Anti-TWEAK autoantibodies were detected in 9/13 (69.2 %) PsoA patients at inclusion and only in 3/57 (5.3 %) healthy blood donors (p < 0.0001). These circulating antibodies were persistent in PsoA patients and detected at similar levels during etanercept therapy. Moreover we showed that they had a down regulating effect on CCL-2 secretion by endothelial cells stimulated by rh TWEAK in vitro. Conclusion Our study revealed that during psoriatic arthritis (1) serum TWEAK was up regulated and (2) TWEAK-binding autoantibodies are generated. Both parameters were not influenced by anti-TNF therapy and persisted at high levels during anti-TNF therapy. For the first time we described here TWEAK-binding IgG autoantibodies with a down regulating effect on CCL-2 secretion by endothelial cells stimulated by rh TWEAK in vitro. Finally, our results suggest that TWEAK may be involved in PsoA pathogeny. Trial registration This clinical trial was approved by the local Ethics Committee "Comité de Protection des Personnes Sud-Méditerranée V" with the registration number: 2011-002954-29, and French health minister registration number AFSSAPS A110784-42 obtained the 08/22/2011. This clinical trial is registered in Clinical trial.gov under the number: NCT02164214